1998
DOI: 10.1016/s0006-3495(98)77778-1
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization Energy of the Initial Electron-Transfer Step in Photosynthetic Bacterial Reaction Centers

Abstract: The reorganization energy (lambda) for electron transfer from the primary electron donor (P*) to the adjacent bacteriochlorophyll (B) in photosynthetic bacterial reaction centers is explored by molecular-dynamics simulations. Relatively long (40 ps) molecular-dynamics trajectories are used, rather than free energy perturbation techniques. When the surroundings of the reaction center are modeled as a membrane, lambda for P* B --> P+ B- is found to be approximately 1.6 kcal/mol. The results are not sensitive to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
109
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(123 citation statements)
references
References 77 publications
11
109
3
Order By: Relevance
“…Recently, Moser et al (42) argued that a value of ϭ 0.7 eV could be maintained for this reaction on the basis of the temperature dependence of the rate, but this reasoning ignored the experimental temperature dependence of ⌬G and required a value for the frequency of the relevant protein modes two times higher than the advocated generic value. Moreover, indications for reorganization energies well Ͻ0.7 eV have been reported for a variety of low-driving force intraprotein reactions (43)(44)(45)(46).…”
Section: Resultsmentioning
confidence: 92%
“…Recently, Moser et al (42) argued that a value of ϭ 0.7 eV could be maintained for this reaction on the basis of the temperature dependence of the rate, but this reasoning ignored the experimental temperature dependence of ⌬G and required a value for the frequency of the relevant protein modes two times higher than the advocated generic value. Moreover, indications for reorganization energies well Ͻ0.7 eV have been reported for a variety of low-driving force intraprotein reactions (43)(44)(45)(46).…”
Section: Resultsmentioning
confidence: 92%
“…Even smaller reorganization energies (λ ∼ 230 meV) have been measured for the porphyrin-fullerene dyads [35]. The initial stages of electron transfer in bacterial reaction centers [36] are also characterized by a low reorganization energy: λ ∼ 70-300 meV, depending on the environment. This is due to the fact that the bacteriochlorophyll molecules (and the molecules of porphyrin involved in our molecular triad) contain highly delocalized π-electron systems.…”
Section: Resultsmentioning
confidence: 99%
“…It has been used in several studies. 16,17,18,19,20,21,22,23,24,25 Several other groups have developed extensions to this theory, as well as other methods to calculate the RE at various levels of theory, including MM, QM/MM, and QM. 20,21,23,26 In particular, it has been shown that the RE in a protein can be estimated from QM or QM/MM calculations on snapshots from classical MD simulations.…”
Section: Introductionmentioning
confidence: 99%